Método heurístico de Pólya como estrategia pedagógica para la resolución de problemas matemáticos - Rodriguez Ayala, Jose Luis (2024)
Pedagogical strategies are essential tools to improve the teaching process and ensure that students learn positively and improve academic performance, that is why Pólya's method is very important in the teaching of mathematics. This study aimed to determine how Pólya's heuristic method as a pedagogical strategy contributes to the resolution of mathematical problems; it was also necessary to investigate how to apply the phases correctly. The research, with a qualitative approach and descriptive scope, had a documentary design; the method of bibliographic review with the indexing technique and the search log, bibliographic cards and content cards as instruments, allowed obtaining information from books, magazines and reliable articles with the purpose of providing an appropriate basis for each one of the study categories. After performing the respective analysis, it was evidenced that this method contributes positively, allowing the development of skills and organization in problem-solving, as well it develops critical thinking and multiple approaches to solving a problem, moreover students feel more self-confident when they follow an organized process from beginning to end. Keywords: Problem-solving, Pólya's method, pedagogical strategy, phases.